(3GdeSFhdjI GdeOfjI GdfGTFI Yf CYeGd GdeQGbHI GdLhjI (B/s - (3LeGd SjO NdjaI eMeOs; (3eMehO GdSjO YHO GdeYWj NjGds; (3LGeYI MdhGfs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb (B- (3LGeYI MdhGf,s, 2012)
(3eQGbHI GdMQcI GdLhjI ef GdYfGUQ GdegeI aj eLGd GdWjQGf GdeOfj GdOhdj, MjK jYJeO YdjgG bGOI GdWGFQGJ dJCejf SdGeI GdQMdI GdLhjI, hfXQkG GdMOGKI CYeGd GdeQGbHI GdLhjI dGJRGd GdeSFhdjI GdfGTFI YfgG HOhf JfXje Ydi GdUYjOjf GdOhdj hGdOGNdj aj CZdH GdHdOGf, hdeG cGf eQGbHh GdLh eYQVjf ddNWC CKfGA eHGTQI CYeGdge, hcGfJ GdbGYOI GdYGeI JbVi HCf cd TNU jchf eSFhdkG Yf JYhjV eG jSHHg aYdg GdNGWF ddZjQ ef VQQ, dPdc JKhQ eSFhdjJge Yf eG JSHHg CaYGdge GdNGWFI ef CVQGQ ddZjQ, hbO GfJgi GdHMK Edi EecGfjI bjGe eSFhdjI CcKQ ef LgI Yf CYeGd GdeQGbHI GdLhjI, abO JfTC eSFhdjI eQGbHj GdMQcI GdLhjI CfaSge, hbO JfTC eSFhdjI GdhcGdGJ GdJj JSJNOe gDdGA GdeQGbHjf, ceG bO JfTC eSFhdjI LgI GdEOGQI Yf gPg GdCYeGd, ceG JHjf GNJdGa GdCSGS GdbGfhfj GdeSFhdjI cd ef gPg GdLgGJ Yf gPg GdCYeGd hPdc JHYkG GdYdGbJgG GdbGfhfjI HGdeVQhQ aaj Mjf JYJHQ eSFhdjI eQGbHj GdMQcI GdLhjI GdbUjQjI OGFekG JNJda eSFhdjI hcGdI GdeQGbHI GdLhjI hLgI GdEOGQI eG Hjf GdeSFhdjI GdYbOjI hGdJbUjQjI(B.s
Air traffic control is one of the critical elements in the field of international civil aviation, and air traffic controllers always at risk of fault during performance their acts, whereas the general rules that decide that each person be responsible for damage compensation caused by his fault, so the responsibility of air traffic controllers arises for damage to others which caused by their faults, and this study are concluded to the possibility of the emergence of more of the responsibility on the actions of air traffic control, from which responsibility of the controllers which always a tort liability, and the responsibility of air traffic control agencies as well as a governmental liability, which may be contractual liability or may be tort, that according to the legal relationship with the injured.
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI MdhGf, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2012.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 653-679(3UaMIs
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3NOeGJ GdedGMI GdLhjIs; (3GdfXGe GdbGfhfj ddWGFQIs; (3NOeGJ GdCQUGO GdLhjIs; (3GdYbO GdahQ hGdeSJeQs; (3GdYbO GdTcdj hGdYjfjs; (3eGgjI YbO GdeQGbHIs; (3YdGbI GdSHHjIs; (3eaghe GdNWC GdhXjajs; (3QSGFd LGeYjIs -- (3LGeYI MdhGfs